(untitled) (Revista Científica Integrada, 2025)
Objective: To identify and evaluate possible strategies to extend the lifespan of a sanitary landfill in the state of São Paulo. Method: The methodology comprised three stages: characterization of the study area, including data collection on the landfill and demographic and territorial information; characterization and quantification of solid waste, based on the analysis of data obtained from public databases; and evaluation of the landfill’s lifespan, conducted through the relationship between the landfill’s available capacity and the projected waste generation. Literature research on disposal and treatment methods suitable for reducing waste sent to landfills supported the proposal of improvements for the municipality. Result: At the time of the study (2023), projections indicated that the estimated lifespan of the landfill under analysis would extend until 2025. The landfill is in its final operation stage and about to reach saturation. When comparing treatments widely used in Brazil, the most compatible and beneficial for the municipality under study is selective collection and its final destinations: reuse, recycling, and organic matter decomposition. Moreover, these strategies contribute to extending the lifespan of landfills and increasing opportunities for alternative energy sources and income generation. Conclusion: Selective collection demonstrates greater potential for the municipality under study. Although the landfill is about to end its lifespan, such measures remain essential to prevent the rapid saturation of future landfills, requiring environmental education, investments in reverse logistics, and selective collection programs.